Upaya Peningkatan Hasil Belajar Melalui Model Pembelajaran Problem Based Learning Siswa Kelas I SDN 39 CakraNegara Tahun Pelajaran 2022/2023 - Qurrata A’yun; Siti Rahmatilah; Sukma Wulandari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to determine the increase in student learning outcomes by applying the Problem Based Learning model using visual media for class I SD. This type of research is classroom action research (CAR) with the Kemmis and Mc Taggart models, each cycle consisting of (1) planning, (2) action and observation, and (3) reflection. The subjects in this study were class students at SD Negeri 39 Cakranegara with a total of 20 students. Data collection techniques used are observation, learning achievement tests and documentation. The instruments used in this study were observation sheets and for the Steps of the Problem Based Learning model aided by visual media and test questions. This study uses completeness analysis and comparative descriptive analysis, namely comparing the pre-cycle, cycle I and cycle II scores. The results showed that student learning, which was initially in the pre-cycle of 37%, in the first cycle of learning increased with a mastery level of 59%. Then it increased again in cycle II to 89% of all students. Student responses tended to be positive where students expressed pleasure in learning using the Problem Based Learning Model. Can improve the learning outcomes of class I SD Negeri 39 Cakranegara.